2007
DOI: 10.1007/s11606-006-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and Acute Renal Failure After Fire Ant Bites

Abstract: We describe a 59-year-old patient who developed acute renal failure because of rhabdomyolysis after extensive red fire ant bites. This case illustrates a serious systemic reaction that may occur from fire ant bites. Consistent with the clinical presentation in rhabdomyolysis associated with non-traumatic causes, hyperkalemia, hypophosphatemia, hypocalcemia, and high anion gap acidosis were not observed in this patient. While local allergic reactions to fire ant bites are described in the literature, serious sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
(11 reference statements)
2
14
0
2
Order By: Relevance
“…This finding is consistent with reported DPH-induced inhibition of I Kr in guinea pig ventricular myocytes and QTc prolongation in healthy volunteers given oral DPH [15]. The IC 50 for blockade of the delayed rectifier potassium current is 30 μM, approximately 40 times therapeutic diphenhydramine concentrations [15]. Again, the DPH concentrations necessary to produce this blockade are unlikely to be achieved with therapeutic dosing, but may be within the range of plasma concentrations achieved in the setting of overdose.…”
Section: What Is the Pharmacology Of Dph?supporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with reported DPH-induced inhibition of I Kr in guinea pig ventricular myocytes and QTc prolongation in healthy volunteers given oral DPH [15]. The IC 50 for blockade of the delayed rectifier potassium current is 30 μM, approximately 40 times therapeutic diphenhydramine concentrations [15]. Again, the DPH concentrations necessary to produce this blockade are unlikely to be achieved with therapeutic dosing, but may be within the range of plasma concentrations achieved in the setting of overdose.…”
Section: What Is the Pharmacology Of Dph?supporting
confidence: 92%
“…A number of snake venoms are associated with rhabdomyolysis, including pit vipers (Subfamily Crotalinae), true vipers (Subfamily Viperinae), sea snakes (Family Hydrophiidae), and Australasian elapids (Family Elapidae) [49]. Rhabdomyolysis has been reported following envenomation by insects of the Order Hymenoptera, including hornets, wasps, honey bees, and fire ants with clinically significant rhabdomyolysis being reported only following multiple stings [50][51][52][53][54]. Rhabdomyolysis has been rarely reported with spider envenomation including that of the genera Latrodectus and Loxosceles [55][56][57].…”
Section: What Other Xenobiotics Cause Rhabdomyolysis?mentioning
confidence: 99%
“…Idealmente debe medirse por radioinmunoensayo, pero el resultado tarda más de 24 horas lo que limita su uso en la práctica clínica. La mioglobina parece tener un papel en determinar el pronóstico de la lesión renal asociada a rabdomiolisis, pero este beneficio no está muy bien establecido (42,43,45,(47)(48)(49).…”
Section: Mioglobinaunclassified
“…En los estadios iniciales la relación BUN/creatinina se encuentra baja por aumento de la creatinina en sangre secundaria al catabolismo muscular; en los estadios tardíos la mioglobina se metaboliza a urea por lo cual la relación BUN/creatinina aumenta en forma desproporcionada con respecto a las lesiones renales por otras causas (15,16,18,23,25,(30)(31)(32)(33)42,43,45,(47)(48)(49).…”
Section: Productos Nitrogenadosunclassified
“…Most studies that describe the clinical aspects of ant stings reported accidents with ants of the genus Solenopsis (Myrmicinae), known as fire ants [20,21,22]. In most serious cases, these accidental encounter with fire ants can promote multiple body rash, seizures, heart failure, and serum sickness nephritis and, more rarely, acute renal failure [23,24].…”
Section: Clinical Aspects Of Ants' Stingsmentioning
confidence: 99%